The Generation Methods and Applications of Cavitating Jet by Using Bubble Collapse Energy - Haida Zhang; Chenxing Fan; Luyao Wang; Wenjun Lu; Deng Li (Energies, 2024)
Cavitation is a dynamic process characterized by the formation, growth, and collapse of vapor or gas vacuoles in liquids or at the liquid–solid interface, initiated by a local pressure drop. This phenomenon releases concentrated energy through microjet impacts and shock waves, leading to a violent exchange of energy with the surrounding environment. While cavitation is often perceived as detrimental, certain aspects can be harnessed for practical applications. Relevant studies have shown that cavitating jets provide high operating efficiencies, reduce energy consumption per unit, and have the potential for waste treatment. This paper presents three types of cavitating jets: central body cavitation, oscillatory cavitation, and shear cavitation. Additionally, the formation process of a cavitating jet and the effects of various factors on jet performance are discussed. Following an in-depth examination of the cavitation phenomena, subsequent chapters explore the applications of cavitating jets in material surface enhancement, cleaning, and energy exploration. Furthermore, recommendations for future research on cavitating jets are provided. This paper provides a comprehensive literature review on cavitating jets.